Measurement of the Effective Refractive Index of Suspensions Containing 5 µm Diameter Spherical Polystyrene Microparticles by Surface Plasmon Resonance and Scattering - Osvaldo Rodríguez-Quiroz; Donato Luna-Moreno; Araceli Sánchez-Álvarez; Gabriela Elizabeth Quintanilla-Villanueva; Oscar Javier Silva-Hernández; Melissa Marlene Rodríguez-Delgado; Juan Francisco Villarreal-Chiu (Chemosensors)
Microplastics (MP) have been found not only in the environment but also in living beings, including humans. As an initial step in MP detection, a method is proposed to measure the effective refractive index of a solution containing 5 µm diameter spherical polystyrene particles (SPSP) in distilled water, based on the surface plasmon resonance (SPR) technique and Mie scattering theory. The reflectances of the samples are obtained with their resonance angles and depths that must be normalized and adjusted according to the reference of the air and the distilled water, to subsequently find their effective refraction index corresponding to the Mie scattering theory. The system has an optical sensor with a Kretschmann–Raether configuration, consisting of a semicircular prism, a thin gold film, and a glass cell for solution samples with different concentrations (0.00, 0.20, 0.05, 0.50, and 1.00%). The experimental result provided a good linear fit with an R2 = 0.9856 and a sensitivity of 7.2863 × <semantics>10−5</semantics> RIU/% (refractive index unit per percentage of fill fraction). The limits of detection (LOD) and limit of quantification (LOQ) were determined to be 0.001% and 0.0035%, respectively. The developed optomechatronic system and its applications based on the SPR and Scattering enabled the effective measurement of the refractive index and concentration of solutions containing 5 µm diameter SPSP in distilled water.